The factors influencing entrepreneurial success among micro entrepreneurs in Kedah - Alauddin, Amylia Hafawati (2024)
The number of micro entrepreneurs in Kedah is gradually increasing nowadays. Numerous prior studies have acknowledged the important position of micro entrepreneur in developing many economies internationally. Despite experience unique challenges, micro entrepreneurs are also able to stimulate social development by offering job opportunities. Thus, it shows that the significance of micro entrepreneurs cannot be overemphasized. However, the data shows that the failure rate for micro entrepreneurs to fail is alarming. Focusing on micro entrepreneurs, current study identifies and examines the possible factors affecting entrepreneurial success. The empirical research entailed quantitative method by questionnaire, then continue to analysed using descriptive analysis, correlation analysis and multiple regression analysis. A total of 380 questionnaires were distributed randomly among micro entrepreneurs specifically in Kedah. The findings demonstrated that financial literacy and entrepreneurial skills have a significant influence towards entrepreneurial success. However, networking did not show any significant influence result towards entrepreneurial success among micro entrepreneurs in Kedah. The result of current study could contribute to the existing body of knowledge and managerial implications.